Buddhist Teen Worldview: Some Normative Background for Health Professionals - Thanissaro, Phra Nicholas (Contemporary buddhism, 2015)
Although there are dangers in essentializing religious practice, to be able to typify the worldviews of healthy Buddhists becomes advantageous when health professionals need to recognize atypical worldviews that are potentially pathological. The paper is an anthology of potentially ambiguous claims expressed by healthy Buddhist teenagers during UK research including outlook on karma, rebirth, meditation, mindfulness, contact with spirit presences, renunciation, spiritual teachers and superstition. The testimony helps clarify diagnosis of identity, well-being and conformity issues, social withdrawal, anxiety and psychotic disorders in Buddhist teens while offering advice on management of ADHD, OCD, substance abuse and depression. While offering normalized background against which health professionals can evaluate spiritual well-being of young Buddhists the paper offers advice for how treatment can be made more culturally sensitive for Buddhists.